Education and Women's Economic Participation through a Gender Lens - Kusumawardhani, Hapsari Ayu; Wardhani, Arisanti Ayu (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to identify research trends regarding the relationship between education and women's participation in the workforce. A qualitative method is employed, using a systematic literature review. Data are collected from the Scopus database, consisting of 114 publication documents from 2000 to 2025. Data analysis is conducted using Vosviewer and Biblioshiny software. The findings show that research on education and women's economic participation has increased, peaking in 2021, with most publications appearing as journal articles in the social sciences. Thematic mapping identifies core research themes such as gender, education, employment, and sustainable development, with notable attention to socio-cultural barriers, technological inequality, and policy interventions. Although women’s educational attainment has improved globally, persistent challenges-such as social norms, limited access to formal employment, and inadequate policy support-continue to hinder their full economic participation. The study also reveals a significant gap in research on women's empowerment in certain sectors and highlights the necessity for cross-sectoral collaboration and further studies in underexplored regions. These findings are essential for strengthening the relationship between education and women’s economic empowerment, supporting inclusive and sustainable economic growth in accordance with the Sustainable Development Goals.